Euro Area Policies : Selected Issues. (IMF Staff Country Reports; Country Report, 2003)
An important aim of this paper is to take shifts in the long-term anchor in the empirical specifications. The study examines exchange-rate pass-through and external adjustment in the euro area. The impact on third-country trade and investment is also discussed. A better understanding of the economic behavior underlying limited pass-through is an important consideration for investigating the implications of currency fluctuations and the pattern of external adjustment. The impulse-response patterns suggest a high degree of local currency pricing in import prices and producer currency pricing in export prices.